Shakespeare and the medieval world - Cooper, Helen, 1947- (Arden critical companions., 2010)
Helen Cooper's unique study examines how continuations of medieval culture into the early modern period, forged Shakespeare's development as a dramatist and poet. Medieval culture pervaded his life and work, from his childhood, spent within reach of the last performances of the Coventry Corpus Christi plays, to his dramatisation of Chaucer in The Two Noble Kinsmen three years before his death. The world he lived in was still largely a medieval one, in its topography and its institutions. The language he spoke had been forged over the centuries since the Norman Conquest. The genres in which he wrote, not least historical tragedy, love-comedy and romance, were medieval inventions. A high proportion of his plays have medieval origins and he kept returning to Chaucer, acknowledged as the greatest poet in the English language. Above all, he grew up with an English tradition of drama developed during the Middle Ages that assumed that it was possible to stage anything - all time, all space.